25th ACM Symposium on Virtual Reality Software and Technology 2019
DOI: 10.1145/3359996.3364817
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Convolutional Neural Networks with Virtual Reality

Abstract: Software systems and components are increasingly based on machine learning methods, such as Convolutional Neural Networks (CNNs). Thus, there is a growing need for common programmers and machine learning newcomers to understand the general functioning of these algorithms. However, as neural networks are complex in nature, novel presentation means are required to enable rapid access to the functionality. For that purpose, this paper examines how CNNs can be visualized in Virtual Reality. A first exploratory stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…During the study selection process, we identified several studies that appeared to meet the inclusion criteria but were eventually excluded: 1) In [14], the authors excluded due to similarity to [11]. 2) In [15], the authors Excluded due to significant overlap in content and authorship with [11]. 3) In [16], the authors excluded due to its focus on visual data mining and representation of data and symbolic knowledge within VR spaces for classification tasks, rather than AI system visualization in VR.…”
Section: E Studymentioning
confidence: 99%
“…During the study selection process, we identified several studies that appeared to meet the inclusion criteria but were eventually excluded: 1) In [14], the authors excluded due to similarity to [11]. 2) In [15], the authors Excluded due to significant overlap in content and authorship with [11]. 3) In [16], the authors excluded due to its focus on visual data mining and representation of data and symbolic knowledge within VR spaces for classification tasks, rather than AI system visualization in VR.…”
Section: E Studymentioning
confidence: 99%